Measuring Productivity of Citrus Hand Harvesters and Assessing Implications on Harvest Costs and Mechanical Harvesting Developments - Fritz M. Roka; Barbara R. Hyman (EDIS, 2013)
Existing mechanical harvesters recover 70 to 95 percent of the available fruit crop. While changes can be made to increase fruit recovery percentages, mechanical systems will never equal the fruit recovery percentages from hand-harvesting crews, much less capture 100 percent of the available fruit. Whether or not to glean (to use manual labor to collect fruit not harvested by the machine) will remain an important question that growers will have to face with every block they choose to mechanically harvest. This study incorporated field harvesting data and developed a model that predicted the extent to which labor productivity would be affected by decreasing the number of oranges available for harvesting by manual labor. Given current market prices of fruit, recovery percentage of crops harvested using mechanical harvesting equipment can improve up to 99 percent and gleaning will remain a profitable activity. This 6-page fact sheet was written by Fritz M. Roka and Barbara R. Hyman and published by the UF Department of Food and Resource Economics, May 2013.